The potential role of the ESRRG pathway in placental dysfunction. Issue 3 (March 2021) - Zou, Zhiyong; Forbes, Karen; Harris, Lynda K; Heazell, Alexander E P
Abstract : Normal placental development and function is of key importance to fetal growth. Conversely aberrations of placental structure and function are evident in pregnancy complications including fetal growth restriction (FGR) and preeclampsia. Although trophoblast turnover and function is altered in these conditions, their underlying aetiologies and pathophysiology remains unclear, which hampers development of therapeutic interventions. Here we review evidence that supports a role for estrogen related receptor-gamma ( ESRRG ) in the development of placental dysfunction in FGR and preeclampsia. This relationship deserves particular consideration because ESRRG is highly expressed in normal placenta, is reduced in FGR and preeclampsia and its expression is altered by hypoxia, which is thought to result from deficient placentation seen in FGR and preeclampsia. Several studies have also found microRNA (miRNA) or other potential upstream regulators of ESRRG negatively influence trophoblast function which could contribute to placental dysfunction seen in FGR and preeclampsia. Interestingly, miRNAs regulate ESRRG expression in human trophoblast. Thus, if ESRRG is pivotally associated with the abnormal trophoblast turnover and function it may be targeted by microRNAs or other possible upstream regulators in the placenta. This review explores altered expression of ESRRG and upstream regulation of ESRRG -mediated pathways resulting in the trophoblast turnover, placental vascularisation, and placental metabolism underlying placental dysfunctions. This demonstrates that the ESRRG pathway merits further investigation as a potential therapeutic target in FGR and preeclampsia.